The magnitude and management of functional constipation at pediatric gastroenterology clinics: A survey study of various countries. Issue 1 (13th September 2021) - Osatakul, Seksit; Benninga, Marc A.; Thapar, Nikhil; Treepongkaruna, Suporn; Puetpaiboon, Areeruk
Abstract: Background and Aim: There have been no large‐scale epidemiological study of functional constipation of pediatric gastroenterology services. This survey was undertaken to investigate the prevalence of functional constipation and magnitude of related problems in hospital settings of various countries as well as the practice of pediatric gastroenterologists in management of these conditions. Methods: The survey was conducted by sending questionnaires to members of Societies for Pediatric Gastroenterology Hepatology and Nutrition of various continents. Results: A total of 274 pediatric gastroenterologists from 41 countries participated in this study. Functional constipation accounted for overall 30% of patients attending pediatric gastroenterology outpatient clinics. In comparison with non‐western countries, respondents from western countries reported significantly higher median annual numbers of new patients with intractable functional constipation (10 [4, 25] vs 5 [2, 10], P < 0.001), dyssynergic defecation (3 [0, 15] vs 1 [0, 4], P < 0.001), and colonic inertia (2 [0, 5] vs 0 [0, 1], P < 0.001). The use of high dose polyethylene glycol for fecal disimpaction was significantly more commonly among respondents from western countries, whereas rectal enema was significantly more favored in non‐western countries. Respondents from different continents reported significant discrepancies in choices of investigations and management of patients with dyssynergic defecation and colonic inertia. Conclusions: Functional constipation is a major problem for pediatric gastroenterology outpatient services worldwide. There were significant variations in the investigations of choice and therapeutic management of functional constipation, intractable functional constipation, and related problems among pediatric gastroenterologists of different geographic regions.